TOLERANSI DALAM SURAH AL-KAFIRUN: KOMPARASI TAFSIR AL-AZHAR DAN HAK DINI KUR’AN DILI - Ghufrani, Azzam; Muhajirin, Muhajirin (Living Islam: Journal of Islamic Discourses, 2024)
This article presents the concept of tolerance using a comparative method from two commentators from different countries and similar historical contexts. Hamka and Hamdi were prominent mufassir and lived during the transition period. Both are related to government and contribute to the continuity of religious life in their respective countries. Surah al-Kafirun, which is a Makkiyah surah, has a strong message about tolerance and religious freedom. Hamka emphasized the importance of maintaining faith and rejecting compromise between monotheism and shirk and emphasized the need to build togetherness and maintain relations between religious communities without sacrificing faith. In the history of his life, Hamka showed a firm attitude towards religious beliefs, including his resignation from the Indonesian Ulema Council because he refused to withdraw the fatwa regarding wishing a Merry Christmas. On the other hand, Elmalılı Hamdi Yazır emphasized the importance of a gentle approach in da'wah and conveying the message of the Qur'an in a good way. His interpretation also reflects the context of the secularization of the Turkish Republic at that time. These two interpretations show differences in approach and historical context, but both agree that tolerance does not mean sacrificing one's beliefs. This research provides in-depth insight into various perspectives in the tradition of interpreting the Koran and how the values of tolerance can be applied in various social and political contexts. Keywords: Religion Moderation, Sekularization, Takfir, Turks   Artikel ini mengemukakan konsep toleransi dengan metode komparatif dari dua mufassir dengan negara yang berbeda dan memiliki konteks historis yang serupa. Hamka dan Hamdi merupakan mufassir terkemuka dan hidup pada masa peralihan pemerintahan. Keduanya memiliki keterkaitan dengan pemerintahan dan berkontribusi dalam keberlangsungan kehidupan beragama di negara masing-masing. Surah al-Kafirun, yang merupakan surah Makkiyah, memiliki pesan kuat tentang toleransi dan kebebasan beragama. Hamka menekankan pentingnya menjaga akidah dan menolak kompromi antara tauhid dan syirik, serta menekankan perlunya membangun kebersamaan dan menjaga hubungan antar umat beragama tanpa mengorbankan keimanan. Dalam sejarah kehidupannya, Hamka menunjukkan sikap tegas terhadap keyakinan agama, termasuk pengunduran dirinya dari Majelis Ulama Indonesia karena menolak menarik fatwa tentang mengucapkan selamat Natal. Di sisi lain, Elmalılı Hamdi Yazır menekankan pentingnya pendekatan yang lembut dalam dakwah dan menyampaikan pesan al-Qur'an dengan cara yang baik. Tafsirnya juga mencerminkan konteks sekularisasi Republik Turki pada masa itu. Kedua tafsir ini menunjukkan perbedaan dalam pendekatan dan konteks historis, tetapi keduanya setuju bahwa toleransi tidak berarti mengorbankan keyakinan sendiri. Penelitian ini memberikan wawasan mendalam tentang berbagai perspektif dalam tradisi penafsiran al-Qur'an dan bagaimana nilai-nilai toleransi dapat diterapkan dalam berbagai konteks sosial dan politik.   Kata kunci: Moderasi Beragama, Sekularisasi, Takfir, Turki